Factors associated with physician burnout syndrome: a comparative analysis - Stojanović, Marko; Rančić, Nataša; Stojanović, Miodrag (Vojnosanitetski pregled, 2025)
Background/Aim. Burnout syndrome (BS) can occur in doctors at different levels of health care. The aim of this study was to identify the prevalence of BS and compare the differences among physicians in health institutions in Southeast Serbia (SES). Methods. A multicenter, questionnaire-based cross-sectional study was conducted among 373 physicians (252 female and 121 male) from primary, secondary, and tertiary care institutions in SES from 2023 to 2024. The Maslach Burnout Inventory-Human Services Survey (MBI-HSS) was applied. Results. A significantly higher score on the emotional exhaustion (EE) subscale was observed in physicians older than 55 years (p < 0.001) and those with more than 25 years of work experience and more than 14.5 years of specialist experience. Higher EE scores were also observed in doctors with specialization (p < 0.001), then, in those in managerial positions (p = 0.031), in doctors with additional engagement in private practice (p = 0.019), those with more than two duties per week (p = 0.008), and physicians who assessed that their greatest job burden was dealing with a large number of patients during the workday (p < 0.001). A significant increase in depersonalization (DP) subscale values was associated with age above 53.5 years, additional engagement in private practice (p = 0.015), shift work (p = 0.049), and physicians who assessed that their greatest job burden was dealing with a large number of patients during the workday (p < 0.001). A significant increase in personal achievement subscale values was observed among doctors in managerial positions (p = 0.004). The highest percentage of physicians from tertiary care institutions had high EE and low personal achievement values, while the highest percentage of physicians from primary care institutions had high DP values. Conclusion. Doctors in health institutions in SES have a moderate degree of BS. Additional research into BS and the factors that contribute to its occurrence is needed, as well as taking appropriate preventive and corrective measures at each of the three levels of health care.